Effect of size particle on palm oil waste for production of bio oil through batch pyrolysis processing - Mohd Hafizi, Mohd Azlan (2009)
The production of bio oil from the pyrolysis of palm oil waste (PKS and EFB) has been studied using a small lab scale pyrolysis unit. The effects of sample preparation (particle size) of the sample on the product yields and compositions were investigated .The effect of sample preparation influence the yield of the bio oil for the sample (EFB and PKS). The highest bio oil yield of PKS was obtained at 400 0C at particle size less than 5mm. For EFB, particle size (length) 5 mm -10 mm of EFB shows the higher yield of bio oil. The various characteristics of the bio oil are accomplished under these conditions and identified by the preliminary experiment conducted by using the thermo gravimetric analyzer (TGA) to determine volatility, ash content, moisture and fixed carbon. The functional groups of the product which is bio oil are identified by using fourier transform infrared spectrometer (FTIR). The chemical characterization studies showed that the bio oil obtained from the sample (PKS and EFB) might be a potentially valuable source as a renewable fuel and for the usage of chemical feed stocks.